YouTube vs. GEMA Musik und Urheberrecht im digitalen Kapitalismus - Stade, Philip (Büchner-Verlag, 2021)
»This video is not available in your country.« With this sentence, the video platform YouTube fueled many years of dispute with the German collecting society GEMA. Numerous online discussions focused on the appropriate remuneration for music streaming - GEMA bashing followed. Music and copyright have always been a contentious issue. Digitization set in motion a process that changed the way music and other creative goods are produced, consumed, distributed and exploited. This break undermined previous business models of the music industry and shook basic assumptions in the understanding of copyright. Philip Stade focuses on the particular online discourse YouTube vs. GEMA and, in the spirit of cultural studies, opens up interdisciplinary and historical perspectives on the fields of music business, copyright and capitalism in the digital transformation. The focus is on hegemonic strategies and the central role of social media. Even though the social and economic upheavals of the digital transformation are far from complete, Stade precisely elaborates which overarching shifts are taking place in the relationship between exclusive control and free access. For we are only just beginning to understand how digital capitalism works.